Bodies of Modernism : Physical Disability in Transatlantic Modernist Literature - Linett, Maren Tova (Book collections on Project MUSE., 2017)
"Bodies of Modernism brings a new and exciting analytical lens to modernist literature, that of critical disability studies. The book offers new readings of canonical and noncanonical writers from both sides of the Atlantic including Flannery O'Connor, Eudora Welty, H.G. Wells, D.H. Lawrence, Elizabeth Bowen, Henry Green, Olive Moore, Carson McCullers, Tennessee Williams, J.M. Synge, Florence Barclay, Virginia Woolf, and James Joyce. Through readings of this wide range of texts and with chapters focusing on mobility impairments, deafness, blindness, and deformity, the study reveals both modernism's skepticism about and dependence on fantasies of whole, "normal" bodies.